Unintentional injuries among children aged 1–5 years: understanding the burden, risk factors and severity in urban slums of southern India - Srujan Lam Sharma (Injury Epidemiology, 2018)
Abstract Background Globally, 5.82 million deaths occurred among children under the age of five years in 2015 and injury specific mortality rate was 73 per 100,000 population. In India, injury specific mortality rate is around 2.1 per 1000 live births contributing to 4% of the total under 5 mortality rate. This study aims to estimate the burden and understand factors associated with unintentional injuries among children aged 1–5 years residing in urban slums of Vellore, southern India. We also attempted to assess the hazards posed by the living environment of these children and study their association with unintentional injury patterns. Methods This cross-sectional study was conducted in eight urban slums of Vellore, southern India and primary caregivers of children aged 1–5 years were interviewed with a questionnaire to obtain the details of injuries sustained in the past three months. Environmental hazard risk assessment was conducted at places frequented by these children and their scores calculated. Baseline prevalence and incidence rates of unintentional injuries were estimated. Multivariate logistic regression and poisson regression analysis were performed to examine factors associated with unintentional injuries and repeated injuries respectively. Association between environmental hazard risk and unintentional injuries was estimated. Results Prevalence of unintentional injuries was 39.1% (95% CI 35.4–42.9%) and incidence rate was 16.5 (95% CI 14.7–18.3) per 100 child months (N = 662). Bivariate analysis revealed that children of working mothers (OR 1.48; 1.01–2.18) and children from overcrowded families (OR 1.78; 1.22–2.60) had increased odds of sustaining unintentional injuries. Multivariate regression analysis revealed that children from overcrowded families had increased odds of sustaining unintentional injuries (AOR 1.66, 95% CI 1.14–2.41). Boys (IRR 1.33, 95% CI 1.07–1.66) and children from overcrowded families (IRR 1.50; 1.14–1.98) were at increased risk of having repeated injuries. There is an increase in incidence rate of injuries with an increased environmental hazard risk, although not statistically significant. Conclusions The burden of unintentional injuries was very high among study children when compared to studies in other urban slums in India. Environment plays an important role in the epidemiology of unintentional injuries; providing safe play environment and adequate supervision of children is important to reduce its burden.